“La lateralidad en el desarrollo de la inteligencia espacial en los niños de educación inicial” - Chiluisa Lescano, Deysi Maribel (2023)
Laterality in the development of spatial intelligence in early childhood education children is fundamental, unfortunately from the educational reality there is a lack of knowledge of didactic strategies to improve this formative process, hence the following research objective "Analyze the importance of laterality in the development of spatial intelligence in early childhood education children of Zumbahua parish, Pujili canton, Cotopaxi province". The qualitative approach guided this research, because of its descriptive nature, the logical method used was inductive, the study population was 48 children and 4 teachers from 4 educational institutions of Zumbahua parish, under the non-probabilistic sampling we worked with the population in question, the techniques used were observation and interview. The results from the point of view of the teachers do not know conceptually and methodologically about the didactic strategies used for the development of laterality in children in early education, directly affecting the learning process, observing that children do not recognize the right and left sides, do not use the digital tweezers correctly, do not develop the calligraphic features correctly, do not codify instructions and do not give solutions to problems. In conclusion, laterality affects the development of spatial intelligence, allows to know the symmetry of the body to be located in space and to place objects or other elements in their mind so it is necessary an adequate intervention and constant work for the improvement of the learning processes of children.